Estudo experimental do comportamento mecânico e da microestrutura de um concreto convencional após simulação das condições de incêndio - Moises Magalhaes de Sousa (2009)
Most of the research for studying concrete in fire uses test methods based on steady state temperature, when occur the stability of temperature in the specimens. As the intensity of the fire does not occur in a standardized manner and affects the concrete in a random way, this situation is best portrayed when the tests are based on the transient temperature, at which there is an heterogeneous distribution of temperature inside the specimens. In this sense, the purpose of this work is to characterize the microstructure and mechanical behavior of concrete used for structural purposes, from the perspective of transient temperature. The specimens are heated to target temperature in accordance with standart fire test methods, from which the specimens are subjected to different cooling (in the water and in the air). The results show a considerable loss of compressive strength from the exposure of concrete to the level of 300°C and the dynamic elastic drops much more greatly with the increase in temperatures. The different types of cooling exercised almost the same influence on the mechanical properties of concrete, and it was possible to visualize, by use of scanning electron microscopy, that the specimens cooled suddenty in water had higher rehydration. Thus, it is belived that the hydration of the concrete, after heating may contribute to the recovery of part the initial mechanical strength.